Intravenous ketamine for postmenopausal women with treatment-resistant depression: Results from the Canadian Rapid Treatment Center of Excellence. (April 2021) - Lipsitz, Orly; McIntyre, Roger S.; Rodrigues, Nelson B.; Lee, Yena; Cha, Danielle S.; Gill, Hartej; Subramaniapillai, Mehala; Kratiuk, Kevin; Lin, Kangguang; Ho, Roger; Mansur, Rodrigo B.; Rosenblat, Joshua D.
Abstract: Women are disproportionately represented amongst samples of adults with treatment-resistant depression (TRD). Ketamine has demonstrated rapid and robust efficacy in adults with TRD. Herein, we sought to determine whether the effectiveness of intravenous (IV) ketamine was influenced by menopausal status in women with TRD. We defined premenopausal women as those under the age of 45 ( n  = 52), while postmenopausal women ( n  = 54) were those over the age of 51. Participants received four IV ketamine infusions over one-to-two weeks at a community-based center for adults with TRD. The primary outcome of interest was the change in depressive symptom severity as measured by the Quick Inventory of Depressive Symptomatology Self-Report 16 (QIDS-SR16 ) following four infusions, compared to pretreatment. The secondary outcomes were improvements in suicidal ideation (SI; i.e., QIDS-SR16 SI item), anxiety (i.e., Generalized Anxiety Disorder-7 scale), anhedonic severity (i.e., Snaith-Hamilton Pleasure Scale), and workplace and psychosocial function (i.e., Sheehan Disability Scale). Menopausal status did not influence overall treatment response, F (4, 280) = 1.83, p  = .123, ηp 2  = 0.025. Both premenopausal and postmenopausal participants demonstrated similar response rates (30% and 26%, respectively) and remission rates (both 13%) to IV ketamine treatment following four infusions. Premenopausal women experienced improvements in social function more rapidly than postmenopausal women, F (2, 174) = 1.65, p  = .047, ηp 2  = 0.019. Postmenopausal women experienced reduction in SI more rapidly than premenopausal women, F (4, 280) = 2.72, p  = .030, ηp 2  = 0.037. These preliminary post-hoc findings provide the impetus for future studies to investigate the moderational role of menopausal status, as defined by hormone levels, on response to IV ketamine for TRD. Highlights: Postmenopausal women with treatment-resistant depression experienced rapid antidepressant effects with IV ketamine. Postmenopausal women experienced anti-suicidality effects of IV ketamine more rapidly than premenopausal women. Premenopausal women experienced improvements in social function with IV ketamine more rapidly than postmenopausal women. Evaluation of safety and efficacy of IV ketamine for peri/postpartum depression may be warranted.